KONFLIK INTERNAL KESULTANAN JOHOR-RIAU PADA MASA PEMERINTAHAN SULTAN ABDURRAHMAN MUAZZAM SYAH I TAHUN 1812-1832 - Febriansyah, Aidil; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The history of the Johor-Riau Sultanate is an important part of the continuity of the Malay Emporium. During the period of 1718-1812 the Sultanate of Johor-Riau experienced many internal conflicts which continued to peak after the death of sultan Mahmud Syah III. In a difficult situation, there was conflict between two people in determining the Sultan's change between Tengku Husien and Tengku Abdurrahman, but in the end Tengku Abdurrahman was elected with the title Sultan Abdurrahman Muazzam Syah I. Sultan Abdurrahman Muazzam Shah I ruled from 1812-1832. The purpose of this study was (1) to find out why the internal conflict of the Johor-Riau Sultanate during the reign of Sultan Abdurrahman Muazzam Shah I. (2) to find out the escalation of internal conflict in the Johor-Riau sultanate during the reign of Sultan Abdurrahman Muazzam Shah I. (3) to knowing the impact of the internal conflict of the Johor-Riau Sultanate during the reign of Sultan Abdurrahman Muazzam Shah I in the field of Politics and Economics. This research used historical methods. The result of this study is that the reign of Sultan Abdurrahman Muazzam Syah I of the internal conflict in the Sultanate of Johor-Riau peak, this was marked by the fragmentation of the Sultanate of Johor Riau into two.Key Words: Conflict, Internal, Johor-Riau Sultanate